Cotas raciais no curso de medicina da UFRGS na perspectiva docente: rupturas e configurações tecidas na garantia do direito à educação superior pública - Nogueira, Fernanda (2015)
The present study focuses on race-based affirmative action policies in higher education admissions. Such policies were established to help achieve democracy in federal universities, providing greater access to higher education for members of historically underrepresented minority groups, such as black students. It aims to analyze the implementation of the race quota system in the Medical School at the Federal University of Rio Grande do Sul UFRGS, from the professors perspective. For that, the following specific goals were designed: (a) identify institutional policies and norms for the access of black students; (b) identify institutional teaching and extension actions as well as actions taken in the Medical course that approach issues related to the black population within Education for Ethnic Racial Relations; and (c) analyze the changes made in the course due to the adoption of racial quota programs, from the professors perspective. The Federal Acts 10,639/2003 and 12,711/2012 are points of reference in this study. The methodology adopted follows a qualitative approach, composed of the analysis of documents, mapping of institutional actions in the Medical course as well as interviews made with eight professors who teach undergraduate courses. The interviews were analyzed through an approach called discursive textual analysis (MORAES; GALIAZZI, 2009). The theoretical background is supported by Fanon (2008), Carvalho (2006), Munanga (1999, 2001; 2005; 2005-2006), Munanga and Gomes (2006), Henriques (2001) and Paixão (2011), who discuss the quota system considering racial inequality in Brazil and its consequences in terms of social inclusion, such as access to public education, by the black population. The results show the occurrence of many ruptures, expressed as changes, interferences, interruptions in actions and practices that used to be common in the course, such as the expression that the race quota program causes interference in the space of power; the production of black invisibility by the professors and the university, marks of difference based on the belief of distinct academic performance by quota and regular students that are not supported by statistical evidence. In a scenario of constant change, some new configurations are revealed in the analysis conducted by the professors when they question teaching and assessment methods, when they recognize the importance of the quota students presence and value the contribution for the diversification of pedagogical and curricular activities. The institutional commitment to expand the discussion about the Afro-Brazilian and the African culture in the academic settings is clear, even though it is still incipient in the Medical course. Finally, the results provide support for the assessment of affirmative action programs within institutions and courses, so that we can go beyond the discussion related to academic achievement and evaluate the success of these policies through an evaluation that conceives these policies as a manner of qualifying the coexistence of distinct actors, identifying and fighting racial discrimination.